A Review of: Boehringer, Sandra 2021. Female Homosexuality in Ancient Greece and Rome. London: Routledge. - Budin, Stephanie (Pnyx: Journal of Classical Studies, 2025)
This is a review of Boehringer's monograph, Female Homosexuality in Ancient Greece and Rome, translated in English and published in 2021 by Routledge.